2011
DOI: 10.1016/j.jvs.2011.03.301
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular therapy for infected aortic aneurysms

Abstract: Endovascular therapy, as a definite treatment for infected aortic aneurysms, provided excellent short- and medium-term results in patients without fistula complications. However, a poorer outcome was evident in patients with fistula complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 26 publications
3
74
0
4
Order By: Relevance
“…In these patients, Vallejo and others reported that a combination (hybrid) of in situ reconstruction and EVT might be necessary. 190,228,[241][242][243][244][245][246][247][248] Subsequent explantation of EVT devices is especially challenging in patients with hybrid procedures and might not be technically feasible. Vallejo and colleagues 190 recommended EVT or hybrid procedures only in selected patients and concluded that open in situ repair remains the surgical management of choice.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…In these patients, Vallejo and others reported that a combination (hybrid) of in situ reconstruction and EVT might be necessary. 190,228,[241][242][243][244][245][246][247][248] Subsequent explantation of EVT devices is especially challenging in patients with hybrid procedures and might not be technically feasible. Vallejo and colleagues 190 recommended EVT or hybrid procedures only in selected patients and concluded that open in situ repair remains the surgical management of choice.…”
Section: Clinical Statements and Guidelinesmentioning
confidence: 99%
“…An endoluminal approach may also be used in cases without clinical evidence of HIV activity and in high surgical risk patients, and that was our choice in Case 1. In similar cases, broad spectrum antibiotics should be used, although treatment duration has not been defined and may last months, years, or the rest of the patient's life 10,7,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for infected aneurysms affecting the thoracic aorta and aortic arch, the surgical procedure typically employs extracorporeal circulation, cardiopulmonary bypass, and even a period of deep hypothermic circulatory arrest (DHCA), further increasing the operative risks. The feasibility of endovascular aortic repair (EVAR) for infected aortic aneurysms has been investigated in numerous studies, which in turn provided encouraging short-term results [18,42,[70][71][72][73][74]. However, the long-term survival and late-onset complications, especially recurrent or persistent infections, are of greater concerns [74].…”
Section: Managementmentioning
confidence: 99%
“…Several studies continuously demonstrated that EVAR is a possible alternative procedure for infected aortic aneurysm patients with high surgical risks, with an early mortality rate less than 20%, which is comparable to that of traditional open repair. A poorer outcome was still evident in patients with aneurysm-related fistulation complication [71,72,[124][125][126][127]. Persistent infection greatly contributed to both early and late mortalities; thus, adjunctive procedures to eliminate contamination and prolonged antibiotic therapy duration after EVAR were usually advocated in the literatures [18,72,74] (see more details in Sections 7.4 and 7.5).…”
Section: Endovascular Techniquementioning
confidence: 99%
See 1 more Smart Citation